2022
DOI: 10.1177/17455057221082954
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal sepsis-related knowledge and reported self-care practices among postpartum women in Dar es salaam, Tanzania

Abstract: Background: Knowledge and reported self-care practices of postpartum women are important for early detection, prevention and treatment of puerperal sepsis. Objectives: This study analyzes the knowledge and self-care practices for prevention of puerperal sepsis and their determinants among postpartum women. Methods: A hospital-based analytical cross-sectional study which included 343 postpartum women was conducted from February to March 2021. Data were collected using interviewer-administered questionnaire. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 33 publications
3
21
1
Order By: Relevance
“…Given that a low educational level was associated with inadequate knowledge and self-care practices regarding puerperal sepsis, this finding suggested that postnatal mothers who did not attend formal education should receive special attention. This is because good knowledge and self-care practices strongly recommend for preventing puerperal sepsis ( 24 ). From a policy perspective, ensuring obstetric caregivers have the knowledge and skills to provide intensive training regarding puerperal sepsis, especially to postnatal women with a low level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a low educational level was associated with inadequate knowledge and self-care practices regarding puerperal sepsis, this finding suggested that postnatal mothers who did not attend formal education should receive special attention. This is because good knowledge and self-care practices strongly recommend for preventing puerperal sepsis ( 24 ). From a policy perspective, ensuring obstetric caregivers have the knowledge and skills to provide intensive training regarding puerperal sepsis, especially to postnatal women with a low level of education.…”
Section: Discussionmentioning
confidence: 99%
“…The nding is higher than the study done in northwestern Ethiopia (40.8%) (10), in Tanzania (11.4%) (11), in Nepal (8.34%) (19), and in Minia University, Egypt (25.3%) (20), had good practice towards prevention of puerperal sepsis.…”
Section: Discussionmentioning
confidence: 63%
“…Data were collected through face-to-face interviews using a structured questionnaire developed from the different literature (10,11). The questionnaire was used to assess reported self-care practice and associated factors among postnatal mothers.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is also one of the direct obstetric causes of death as seen in studies by Suresh et al 3,14 This may be because of increased prevalence of anemia, multiple referrals leading to repeated examinations increasing chances of sepsis and last but not the least injudicious use of higher antibiotics even though not required. [15][16][17] As a result of this, over the recent years resistance to antibiotics have been observed. Also, critical patients requiring prolonged ventilatory support acquire ventilator acquired pneumonia resulting in sepsis and death.…”
Section: Discussionmentioning
confidence: 94%